Andri Yunus: Paradoks dalam Negara Hukum Indonesia - Aulia Yaswita; Syaita Novidia (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The acid attack against Andre Yunus constitutes an act of violence prohibited under statutory regulations and results not only in severe physical suffering but also in significant psychological, emotional, and social impacts on the victim. Such an act can be classified as a violation of human rights, particularly the right to life, the right to personal security, and the right to be free from torture, cruel treatment, and degrading punishment. Acid attacks often leave long-term consequences that affect the victim’s quality of life, social interactions, and ability to carry out daily activities. This study aims to analyze the case from a human rights perspective and to evaluate the extent of the state’s responsibility in providing protection, justice, and recovery for the victim. The research employs a normative legal method using statutory and conceptual approaches to examine relevant legal provisions and human rights principles. The findings indicate that acid attacks constitute a serious crime and a grave violation of human rights, reflecting weaknesses in both preventive and repressive legal protection mechanisms. Furthermore, the fulfillment of victims’ rights remains inadequate, particularly regarding medical rehabilitation, psychological recovery, compensation, and guarantees of long-term protection. Therefore, stronger state commitment is required to ensure effective victim protection and the realization of justice.